National Football League Strategies Business Expansions, Relocations, and Mergers - Jozsa Jr., Frank P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This Brief identifies and contrasts the groups of expansion franchises and any teams that relocated from one metropolitan area or city to another within the National Football League (NFL) during three distinct periods from 1920 to 2013. It discusses historical differences and similarities between the teams$1 (Bmarkets and performances before 1933 and then as members of the NFL$1 (Bs divisions and conferences. It measures and compares the emergence, development and success of the teams by analyzing demographic, economic and sport-specific data. It also discusses the NFL$1 (Bs mergers with the All American Football Conference (1950) and American Football League (1970), outlining the reasons for and consequences of these mergers as well as their significance for sports fans and markets. The book makes an important, relevant and useful contribution to the literature regarding professional sports operations and to the NFL$1 (Bs short and long run business strategies in American culture. Besides numerous sports fans within metropolitan areas and extended markets of these NFL teams, the book$1 (Bs audiences are sports historians and researchers, college and public libraries and current and potential NFL franchise owners and team executives. The book may also be used as a reference or supplemental text for college and university students enrolled in such applied undergraduate and graduate courses and seminars as sports administration, sports business and sports management.s
Keywords: Economics; Industrial organization (Economic theory).; Microeconomics; Economics/Management Science; Economics/Management Science, general; Industrial Organization; Microeconomics